Study on the Growth of Lactic Acid Bacteria (LAB) from Dadih in Ice Cream as Probiotic Food - Ambri, Khairul; Kusnadi, Joni; Putri, Widya Dwi Rukmi (Fakultas Teknologi Pertanian Universitas Brawijaya, 2009)
Dadih is West Sumatera traditional food made by natural fermentation of buffalo milk in bamboo which contains some Lactic Acid Bacteria (LAB). Some of these bacteria in dadih have probiotic characteristic therefore can be used as probiotic resources. LAB have good effect on the health if they fulfill qualitative and quantitative requirement as probiotic, such as viable and able to maintain their viability during consumption with minimum number of cell of 1X106 CFU/ml. One of the effort to maintain viability of LAB and to have minimum quantitative requirement of LAB as probiotic food is LAB from dadih is cultivated in suitable media. Ice cream is one of an appropriate media for LAB from dadih to grow.The research was conducted in Randomized Block Design with two factors. The first factor was incubation time consisted of three levels: 0, 5, and 10 hour, whether second factor was aging time consisted of three levels: 24, 48, and 72 hours.Preliminary experiment showed that LAB from dadih grew well in ice cream. Initial number of LAB in ice cream mix after addition of 5% starter was 5.5 x 107 CFU/ml whether average number of LAB in final product (ice cream) were in range of 8.9 x 107 CFU/ml – 7.8 x 1013 CFU/ml. The result showed that the best treatment based on microbiological and physicochemical characteristic was treatment with incubation time of 10 hours and aging time of 72 hours. The characteristics of the ice cream were as followed: total number of LAB of 7.76 x 1013 CFU/ml; total sugar of 2.06%; total acid of 0.76%; pH of 4.93; overrun of 11.45% and melting rate of 0,99 g/min whether the best treatment based on sensory characteristic had total amount of LAB of 2.04 x 1011 CFU/ml; total sugar of 2.23%; total acid of 0.72%; pH of 5.07; overrun of 13.04%, and melting rate of 1.00 g/min.Keywords: dadih, probiotic, incubation time, aging time